Brief Report: Plasma Concentrations of Perfluorooctane Sulfonamide and Time-to-pregnancy Among Primiparous Women. Issue 5 (September 2016) - Whitworth, Kristina W.; Haug, Line S.; Sabaredzovic, Azemira; Eggesbo, Merete; Longnecker, Matthew P.
Abstract : Background: A previous study reported a negative association between perfluorooctane sulfonamide (PFOSA) concentrations and fecundability. Methods: We examined this association among women enrolled in the Norwegian Mother and Child Cohort Study (MoBa), in 2003–2004. This analysis was restricted to 451 primiparous women to avoid bias due to previous pregnancy. Self-reported time-to-pregnancy (TTP) and plasma were obtained around 18 weeks of gestation. Approximately half of the women had measurable PFOSA levels; missing values were multiply imputed. We used the logistic analogue of discrete-time survival analysis to examine the adjusted association between PFOSA, other perfluoroalkyl substances, and TTP. Results: The median-measured PFOSA concentration was 0.03 ng/ml (interquartile range = 0.02, 0.07). The age and body mass index-adjusted association between an interquartile distance increase in PFOSA and TTP was 0.91 (95% confidence interval = 0.71, 1.17). Imputation of missing PFOSA resulted in similar estimates. No association was observed with other perfluoroalkyl substances. Conclusion: Based on a weakly decreased fecundability odds ratio, we found only limited support for an association between plasma PFOSA concentrations and TTP among primiparous women. See Video Abstract athttp://links.lww.com/EDE/B79 . Abstract : Supplemental Digital Content is available in the text.